Identifying The Types Of Marketing And Sale Of Carpets And Rugs Of Ilam Province Entrepreneurs - Majidi, Maryam; Eidi, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study is to identify ways of marketing and sales of carpets and rugs entrepreneurs in Ilam province. This research is descriptive-correlation method that has been conducted in field. The target population in this study consisted of scholars, experts, hand-made carpets and rugs, in Ilam province to 120 people. Due to the limited population of the province in the field of hand-made carpets and rugs allcensus, the census is used. The gathered data from two questionnaires with 28 questions is mixed marketing and sales entrepreneurial questionnaire that included questions is 9, was used. Their Cronbach’s alpha is 0.76 and 0.78, respectively. To analyze the data, t-test was used to rank single group and Friedman. Data analysis was performed using software spss22. The results showed that advertising is the key to selling hand-made carpets and rugs. After that, the second is the distribution channel and price and the factors related to the product ranked third and fourth.
Keywords: marketing; sales; carpets and rugs